A Case of Cryptogenic Organizing Pneumonia (COP)- Atypical Presentation (Indian Journal of Case Reports, 2025)
We report a case of cryptogenic organizing pneumonia (COP) with rare radiological presentation. A 29-year-old female presented to us with symptoms of progressive breathlessness and dry cough for 3 weeks. Chest X-ray showed bilateral all zones non-homogenous opacities. She was treated in an outside hospital with antibiotics and was referred to us as the symptoms progressed. High-resolution computed tomography of the chest revealed bilateral diffuse ground glass opacities in a centrilobular pattern involving all the lobes. Fiber-optic bronchoscopy with transbronchial lung biopsy was done. Histopathological examination (HPE) was consistent with organizing pneumonia. Additional investigations could not delineate a specific cause. Hence, the patient was diagnosed with COP. She was treated with immunosuppressants. The patient improved clinically, and subsequent Chest X-rays showed radiological improvement. COP is a rare disease and is suspected when there is no response to routine management along with the typical radiological picture. Our patient presented with atypical radiological presentation. Tissue biopsy and HPE helped us to arrive at a diagnosis. Prompt treatment aided in an uneventful outcome.